Introduction to intelligence : institutions, operations, and analysis - Acuff, Jonathan M.; Craft,Lamesha; Ferrero,Christopher J; Fitsanakis,Joseph; JR.,Richard J. Kilroy; Smith,Jonathan (Washington, D.C. : CQ Press, A Division of Sage, 2022)
"Introduction to Intelligence: Institutions, Operations, and Analysis offers a strategic, international, and comparative approach to covering intelligence organizations and domestic security issues. Written by multiple authors, each chapter draws on the author's professional and scholarly expertise in the subject matter. As a core text for an introductory survey course in intelligence, this text provides a comprehensive introduction to intelligence, including institutions and processes, collection, communications, and common analytic methods"--
Introduction -- Intelligence history -- Intelligence and security institutions: organizations and processes -- Comparative intelligence systems -- Intelligence operations -- Counterintelligence -- Covert operations -- Cyberspace operations and the information environment -- Intelligence regulation and governance -- Inter-agency communications -- Intelligence analysis -- Analytic methods -- The ethics of intelligence -- Threats to the United States and its interests.
Includes bibliographical references and index.
Keywords: Intelligence service; Intelligence officers; International relations